Heritage and Territory: Revaluation of Ashaninka Architecture in the Central Jungle of Peru - Gonzales Reategui , Hilter Alfredo (2025)
This essay is intended to highlight the value of the construction processes used in traditional Ashaninka architecture in the central jungle region of Peru. Paradoxically, these ways of living and building, which have the potential to be a feature of identity and heritage, are undervalued by both locals and outsiders. Recognizing and reevaluating alternative ways of interacting with the environment can be a path not only to healing for a people who have always been marginalized, but also to possible solutions to current problems in contemporary architecture. We will first define the concepts of heritage and territory, followed by a brief overview of the history of the VRAEM and the Ashaninka way of relating to the territory. We will then describe the construction processes of Asháninka architecture and finally offer some brief reflections on the subject